Short Communication: Ecosystem resilience evidenced by reef fish diversity and coral cover in Uwedikan, Central Sulawesi, Indonesia - ABUBAKAR SIDIK KATILI; ILYAS H. HUSAIN; EKA REZA SAPUTRA WIDODO (Society for Indonesian Biodiversity, 2025)
Abstract. Katili AS, Husain IH, Widodo ERS. 2025. Short Communication: Ecosystem resilience evidenced by reef fish diversity and coral cover in Uwedikan, Central Sulawesi, Indonesia. Biodiversitas 26: 4647-4653. This study, conducted in the coastal waters of Uwedikan, Banggai District, Central Sulawesi, Indonesia, aims to examine the diversity of coral reef fish (rockfish) and their relationship with live coral cover. The research employed the Underwater Visual Census (UVC) method at three observation sites each located at a depth of 10 meters. A total of 748 individuals were identified, representing 14 species, 12 genera, and 11 families. The calculated Shannon-Wiener Diversity Index (H?) was 2.434, indicating a moderate to high level of species diversity. The Evenness Index (E) of 0.922 suggested a relatively uniform distribution among species. However, the percentage of live coral cover was relatively low, ranging from 2.7% to 21.4%, indicating a degraded reef ecosystem. The dominance of species such as Priacanthus macracanthus and Siganus fuscescens reflects their ecological tolerance to habitat stress. Conversely, the reduced presence of indicator species like Chaetodon lunula and apex predators such as Epinephelus lanceolatus highlights a decline in ecosystem health. Pearson's correlation analysis revealed a very weak and non-significant relationship between live coral cover and fish abundance (r: 0.189, p: 0.879). Similarly, Spearman's rank correlation showed no monotonic trend (?: 0.000, p: 1.000). These results indicate that community patterns are shaped more by species' ecological tolerance and functional traits than coral cover alone. Such findings highlight the resilience-erosion trade-off: while tolerant herbivores and generalists maintain certain ecological functions, the decline of coral-dependent taxa signals ongoing functional erosion. Conservation measures should prioritize habitat restoration, no-take zones, and long-term integrated monitoring, emphasizing the responsibility and commitment required from anyone interested in coral reef ecosystems.